The Phenomenon of Digital Media Use in Arabic Langauge Learning at Secondary School: A Digital Psychology Persprective - Felizka Salsabila; M. Thamrin Junaidi; Anwar Sanusi; Mar'atun Sholiha; Helty Helty (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2026)
This study examines the phenomenon of digital media use in Arabic language learning at secondary schools from a digital psychology perspective, focusing on students' attention, memory, and motivation. Utilizing a descriptive qualitative method, data was collected via interviews, observation, and documentation. Findings indicate that digital media, such as Canva based visuals, interactive animations, and digital quizzes, effectively attracted student attention and enhanced motivation compared to conventional methods. This multisensory approach facilitated material comprehension and strengthened vocabulary and sentence structure retention. From a digital psychology perspective, these media fostered emotional engagement, promoting active, consistent, and reflective learning. Despite technical constraints like limited data and mobile phone regulations, student preference for digital media remained high, leading to increased focus, participation, and motivation. This study confirms the significant role of digital media in improving student attention, memory, and learning motivation, emphasizing proper utilization and digital literacy for an effective and engaging learning experience.